Endovascular Closure of Secondary Septal Defect in Children with Low Body Weight - Ditkivskyy, Igor O.; Voloshyn, Denys L.; Yermolovych, Yuliia V.; Perepeka, Iryna A.; Lazoryshynets, Vasyl V. (Ukrainian Journal of Cardiovascular Surgery, 2022)
The aim. To assess the effectiveness and safety of transcatheter closure of a secondary atrial septal defect (ASD) using an occluder in symptomatic children weighing ≤10 kg. Materials and methods. In the period from November 2014 to June 2021, on the basis of the National Amosov Institute of Cardiovascular Surgery of the National Academy of Medical Sciences of Ukraine, closure of secondary ASD using an occluder was performed in 18 patients, among them 13 women (72.2%) and 5 men (27.8%). Th e mean age of the patients was 18.94±9.44 months (the youngest patient was 12 months, the oldest was 4 years). The mean weight was 9.294±1.170 kg (6.4 kg to 10 kg), the mean Z-score was -1.7±1.5 (-4.6 to 0.46), the mean height was 80 cm (71 cm to 88 cm). According to the measurements by transesophageal echocardiography (TEE), the average size of the defects was 13.7 mm±3.6mm (the largest 18.0 mm, the smallest 6.0 mm). Results and discussion. In our publication, the effectiveness of the method was 100% (18/18), while the world statistics show 94-95%. Th e frequency of complications was 5.6% (n=1). We suggest that this is associated with the use of a sizing balloon and careful selection of the device. When choosing treatment tactics for symptomatic children weighing ≤10 kg, the decisive factor was the determination of the presence of edges and the size of the defect. Defects were considered suitable for closure, according to TEE data, when all margins of the defect were ≥4 mm, except for the aortic margin. Although the total length of the interatrial membrane was taken into account, it was not of decisive importance, since for most occluders with the presence of all edges, the fields of the implant could not interfere with the work of the anatomical structures of the heart. To determine the real size of the defect, we recommend a measuring balloon under TEE control. The following devices were used to close the defect: MemoPart ASD occluder, Amplatzer Septal Occluder, LifeTech HeartR Occluder, LifeTech HeartR Multi-Fenestrated Atrial Septal Defect (MF-ASD) Occluder. Conclusion. After the study, we are convinced that the endovascular method of closing a hemodynamically significant secondary ASD for the treatment of children with a body weight of ≤10 kg has proven to be an effective method, with successful implantation of the occluder in 100% of cases.